2017
DOI: 10.1302/2058-5241.2.150041
|View full text |Cite
|
Sign up to set email alerts
|

The current situation in hip arthroscopy

Abstract: Hip arthroscopy is an evolving surgical technique that has recently increased in popularity.Although femoroacetabular impingement was an important launch pad for this technique, extra-articular pathology has been described through hip endoscopy.Good clinical results in the medium term will allow improvements in this technique and increase its indications.Cite this article: EFORT Open Rev 2017;2:58-65. DOI: 10.1302/2058-5241.2.150041

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Some studies point to an increase of 250 to 365% in the last 10 years. [19][20][21] This massive increase should raise some concern about indications, patient selection, and proper understanding of the impingement mechanism before deciding on surgical treatment of a painful hip. We believe hip arthroscopy is becoming very popular due to the fast recovery and return to sports activities but also because it is very attractive to opt for surgery in the presence of an "image-based" diagnosis of an isolated labral tear.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies point to an increase of 250 to 365% in the last 10 years. [19][20][21] This massive increase should raise some concern about indications, patient selection, and proper understanding of the impingement mechanism before deciding on surgical treatment of a painful hip. We believe hip arthroscopy is becoming very popular due to the fast recovery and return to sports activities but also because it is very attractive to opt for surgery in the presence of an "image-based" diagnosis of an isolated labral tear.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hip arthroscopy has become a common surgical procedure in both the diagnosis and treatment of painful hip disorders. Arthroscopic hip treatments typically result in good clinical outcomes, with low rates of complications and relatively rapid rehabilitation [ 1 , 2 ]. However, pain around the hip joint may originate from different locations, including extra-articular origins and the lumbar spine [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As well, with the advent of more advanced imaging 15 and the increased utilization of hip arthroscopy, diagnosis of intra- and extra-articular hip and groin conditions has become more precise. 14 In addition, prior studies have found retired professional athletes to be at an increased risk of both knee 1,17 and hip osteoarthritis, 17 though these studies did not include basketball players.…”
mentioning
confidence: 99%